2023
DOI: 10.1039/d2ea00053a
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of nitrophenols in gas phase and aqueous environment: a potential daytime source for atmospheric nitrous acid (HONO)

Abstract: Daytime nitrous acid (HONO) source in the atmosphere has attracted great research attention due to its important role in determining the concentrations of OH radicals, O3, and secondary organic aerosols...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…A similar method was previously employed for 2-and 4nitrophenol. 42 The bracketed term is the square of the spin− orbit coupling (SOC) matrix elements that can be calculated…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar method was previously employed for 2-and 4nitrophenol. 42 The bracketed term is the square of the spin− orbit coupling (SOC) matrix elements that can be calculated…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The rates of ISC, k ISC n , between the first excited singlet state, S 1 , and the lower-energy triplet states, T n ( n = 1–3), can be expressed using Fermi’s golden rule k normalI normalS normalC n = 2 π | false⟨ normalΨ S 1 ( Q 0 ) | S O | normalΨ normalT n ( Q 0 ) false⟩ | 2 · ρ ( Δ E , λ , T ) A similar method was previously employed for 2- and 4-nitrophenol . The bracketed term is the square of the spin–orbit coupling (SOC) matrix elements that can be calculated directly in Q-Chem.…”
Section: Methodsmentioning
confidence: 99%
“…Already 2 decades ago, direct photolysis of gas-phase ortho-nitrophenol (o-NP) was identified as a potential important source of ambient HONO, with possible further implications in the oxidative capacity of the atmosphere (Bejan et al, 2006). Later on, this photolysis reaction has been investigated in many laboratory (Bejan et al, 2007;Wei et al, 2008;Sangwan and Zhu, 2018), theoretical (Vereecken et al, 2016;Guo and Li, 2022), and combined experimentaltheoretical studies (Cheng et al, 2009;Nitta et al, 2021), which further suggested that besides nitrogen release, • OH can also form directly during the photolytic degradation of gaseous o-NP, resulting in aromatic nitroso products. In a recent field study conducted in an urban environment, however, a minor role has been attributed to this second pathway (Cheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important pathways leading to the observed photoproducts, excited triplet state formation followed by nitro-nitrite rearrangement was proposed, yielding the corresponding phenoxy radical and NO after the O-NO bond cleavage (Chen et al, 2005). In addition, the second pathway of photoinduced aqueous-phase nitrophenol denitration accompanied by the HONO release has been studied by several authors (Chen et al, 2005;Barsotti et al, 2017;Guo and Li, 2022). Different mechanisms have been proposed for this step, yielding whole range of speculative reaction products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation